(3cJGH GdbVGAs - (3eQJVi Hf eMeO Cejf GdORahdj GdCfUGQj, J (B1281 (3g` s
(3ChdgG (B:s
(3cJGH GdbVGA hebGUOI KdKI (B((3KdGKg(B) (3GdChd ai GdbGVi s
(3BNQgG (B:s
(3ai EaGOJg GdPi Gdec GdhGbYi ef GdGMJeGdGJ HNdGa JfRjd GdTQGA s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B201s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis